Traditional herbal medicine - A Ziai (Institue of Medicinal Plants, ACECR, 2002)
The earliest indications of medicinal plant use by humans were found in the Middle East and date back to the Stone Age. Travelers and traders introduced Greek and Roman Curative Practices to Indian & Chinese Practitioners, who blended them with their even older ones. Reintroduced by knights returning from the Crusades, these modified practices energized medieval European medicine and the Unani Medicine al Muslims. This cross- pollination of ideas and theories between European and Asian Cultures regarding medicinal plants helped advanced knowledge about plants and somewhat standardize their uses. Books cataloging medicinal plants helped preserve, disseminate and standardize this knowledge.